Egységtörekvések a magyar lutheránus és kálvinista egyházban a 19. század első felében - LUKÁCS, Olga (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2015)
Unifying Attempts within the Hungarian Lutheran and Calvinist Churches in the Beginning of the 19th Century. In the years of the Enlightenment Habsburg politics of religions brought the aforementioned Hungarian Protestant churches closer to each other. Just before the 1848 revolution, the Hungarian Reformed and Lutheran churches were moving towards a union with great enthusiasm. Starting with the beginning of the 18th century it was customary that after joint discussions on several issues the lay representatives of the two churches handled unanimously in the best interest of the church. During the Synods of Buda and Pest in 1791 attempts have been made to establish structural links between the two churches. Starting with the 1840’s years the two churches were nearing each other in the field of schools and education. The Lutheran Church Superintendent Count Károly Zay proposed the idea of unifying the two churches in the “ Társalkodó” journal in 1841. The concept was welcomed enthusiastically mainly by the Lutheran church leaders. All the more so because through this union they were hoping to counterbalance the Pan-Slavic spirited, Slovak nationality current that was increas- ingly strengthening within their own church since 1820. Lajos Kossuth, being himself a Lutheran, also made the“Pesti Hírlap” (The Pest Gazette) available for literary discussion on the topic of the union. On the other hand, however, the enthusiasm the Reformed Church was more restrained. Nevertheless, there have been renowned advocates of the idea within the Reformed Church as well, such as András Fáy (1786-1864). As an estate-owner, Fáy was the Council Judge of the Transdanubian Church District and the Curator of the Church of Pest. As such, he actively participated in church administration, and successfully fought against some hierarchical aspirations and also advocated parity. After a longer period of literary preparations, the representatives of the two churches have begun the treaties. In principle, both sides accepted the union and appointed a joint committee to draw up a detailed plan of the union. Nevertheless, the practical implementation of the plan has proven to be much more difficult. Especially the Transtibiscan Church District (with its centre in Debrecen), declared its averseness against the unification. This was mainly due to dogmatic reasons and to fearing for the financial autonomy of the Reformed Church. But, most of all, it was due to the fact that the unification of the two churches was mainly supported by the time’s lay leaders. András Fáy’s union plan ultimately failed. The 1842 union plan was subject of the press for a few years more. The practical use of the unifying attempts was shown in the launching of the Protestáns Egyház és Iskolai Lap (Protestant Church and School Journal) edited by the Lutheran minister of Pest József Székács and the Reformed minister in Pest Pál Török. Later, however, the two churches have implemented some of the unification plans: the founding of a common Theological Institute in Budapest in 1855, the joint Grammar School in Rimaszombat (Rimavská Sobota), some jointly organized and maintained parishes. At the same time, the two churches agreed on mutually providing pastoral care to the Protestants living in the diaspora and their joint involvement in home and foreign mission activities. Facts that prevented the Hungarian Protestant church union The most common reason was the selfishness on the Calvinist part and the racial and dogmatic jealousy on part of the Lut Although for a short time, the concept of the union was linked to the College of P Thus, all the colleges and their supporting bodies, who saw the establishment of the Pest College as a competition, discarded the idea. The greatest aversion was shown towards the attempts of ethnic assimilation and religious unity, as beyond external unification internal fusion was sought, for which the era was not yet ready.